# More Exercises ## 1.3.K > Note: I think this is an exercise about base change. **Part a**: For $M$ an $A{\hbox{-}}$module and $\phi: A\to B$ a morphism of rings, give $B\otimes_A M$ the structure of a $B{\hbox{-}}$module and show that it describes a functor $A{\hbox{-}}\text{Mod}\to B{\hbox{-}}\text{Mod}$. Solution - $B\otimes_A M$ makes sense: $B$ is a $(B, A){\hbox{-}}$bimodule with the usual multiplication on the left and the right action ` \begin{align*}\begin{align*} A &\to { \operatorname{End} }(B) \\ a &\mapsto (b\mapsto b\cdot \phi(a)) .\end{align*}\end{align*} `{=html} - $B\otimes_A M$ is a left $B{\hbox{-}}$module via the following action: ` \begin{align*}\begin{align*} B &\to { \operatorname{End} }(B\otimes_A M) \\ b_0 &\mapsto (b\otimes m \mapsto b_0 b \otimes m) .\end{align*}\end{align*} `{=html} - This describes a functor: ` \begin{align*}\begin{align*} F: A{\hbox{-}}\text{Mod} &\to B{\hbox{-}}\text{Mod} \\ X &\mapsto B\otimes_A X \\ (X\xrightarrow{f} Y) &\mapsto (B\otimes_A X \xrightarrow{\operatorname{id}_B \otimes f} B\otimes_A Y) .\end{align*}\end{align*} `{=html} - Need to check: - Preserves identity morphism, i.e. $X\in A{\hbox{-}}$Mod implies $F(\operatorname{id}_X) = \operatorname{id}_{F(X)}$ in $B{\hbox{-}}$Mod. - Preserves composition: $F(f\circ g) = F(f) \circ F(g)$. - Preserving identity morphisms: - By construction $X{\circlearrowleft}_{\operatorname{id}_X}$ maps to $B\otimes_A X \xrightarrow{\operatorname{id}_B \otimes\operatorname{id}_X} B\otimes_A X$, can argue that this is the identity map for $B{\hbox{-}}$modules. - Preserving composition: ` \begin{align*}\begin{align*} (X\xrightarrow{f} Y \xrightarrow{g} Z) \mapsto (B\otimes_A X \xrightarrow{ \operatorname{id}_B\otimes f} B\otimes_A Y \xrightarrow{\operatorname{id}_B \otimes g} B\otimes_A Z) = (B\otimes_A X \xrightarrow{\operatorname{id}_B \otimes(g\circ f)} B\otimes_A Z ) .\end{align*}\end{align*} `{=html} > Note: not sure if there's anything to show here. **Part b**: If $\psi: A\to C$ is another ring morphism, show that $B\otimes_A C$ has a ring structure. Solution: - Note $B\otimes_A C$ makes sense, since $C$ is a left $A{\hbox{-}}$module via $a\mapsto (c\mapsto \psi(a)c)$. - Need to define $(B\otimes_A C, P, M)$ such that it's an abelian group under $P$ (plus), a monoid under $M$ (multiplication), and left/right distributivity. - Start by defining on cartesian products: ` \begin{align*}\begin{align*} P: \qty{B\otimes_A C}^{\times 2} &\to B\otimes_A C \\ P\qty{ (b_1 \otimes c_1), (b_2\otimes c_2)} &= (b_1 +_B b_2) \otimes(c_1 +_C c_2) ,\end{align*}\end{align*} `{=html} ` \begin{align*}\begin{align*} M: \qty{B\otimes_A C}^{\times 2} &\to B\otimes_A C \\ M\qty{ (b_1 \otimes c_1), (b_2\otimes c_2)} &= (b_1 \cdot_B b_2) \otimes(c_1 \cdot_C c_2) .\end{align*}\end{align*} `{=html} - Check $A{\hbox{-}}$bilinearity: ` \begin{align*}\begin{align*} P(a\cdot (b_1\otimes c_1),\, (b_2\otimes c_2)) &\coloneqq\qty{ a \cdot (b_1 + b_2)} \otimes(c_1 + c_2) \\ &= \qty{ (b_1 + b_2)} \otimes a\cdot (c_1 + c_2) \quad\text{since $C$ is a left $A{\hbox{-}}$module} \\ &\coloneqq P((b_1\otimes c_1),\, a\cdot (b_2\otimes c_2)) .\end{align*}\end{align*} `{=html} ` \begin{align*}\begin{align*} M(a\cdot (b_1\otimes c_1),\, (b_2\otimes c_2)) &\coloneqq\qty{a\cdot (b_1 \cdot b_2)} \otimes(c_1 \cdot c_2) \\ &= (b_1 \cdot b_2) \otimes\qty{ a\cdot (c_1 \cdot c_2) } \quad\text{since $C$ is a left $A{\hbox{-}}$module} \\ &\coloneqq M((b_1\otimes c_1),\, a\cdot (b_2\otimes c_2)) .\end{align*}\end{align*} `{=html} - So these lift to maps out of $(B\otimes_A C)^{\otimes 2}$. - $P$ forms an abelian group: clear because $+_B, +_C$ do, and commuting is just done within each factor. - $M$ forms a monoid: clear for some reason. - Checking distributivity, claim: it suffices to check on elementary tensors and extend by linearity? ` \begin{align*}\begin{align*} (b_0 \otimes c_0) \cdot \qty{(b_1 \otimes c_1) + (b_2\otimes c_2) } &= (b_0\otimes c_0) \cdot \qty{ (b_1 + b_2) \otimes(c_1 + c_2) } \\ &= (b_0(b_1 + b_2)) \otimes( c_0(c_1 + c_2)) \\ &= (b_0 b_1 + b_0 b_2) \otimes(c_0 c_1 + c_0 c_2) \\ &= \cdots .\end{align*}\end{align*} `{=html} ## 1.3.L If $S\subseteq A$ is multiplicative and $M\in A{\hbox{-}}$Mod, describe a natural isomorphism ` \begin{align*}\begin{align*} \eta: (S^{-1}A)\otimes_A M \to (S^{-1}M) \end{align*}\end{align*} `{=html} as both $S^{-1}A{\hbox{-}}$modules and $A{\hbox{-}}$modules. Solution - Recall the definition ` \begin{align*}\begin{align*} S^{-1}A\coloneqq\left\{{ {a\over s} {~\mathrel{\Big\vert}~}a\in A, s\in S}\right\} / \sim \\ {a_1 \over s_1} \sim {a_2 \over s_2} \iff \exists s\in S \text{ such that } s\qty{ s_2 a_1 - s_1 a_2 } = 0_A .\end{align*}\end{align*} `{=html} - Similarly $S^{-1}M = \left\{{{m\over s}}\right\}/\sim$. The universal property: in $A{\hbox{-}}$Mod, $M\to S^{-1}M$ is initial among all morphisms $\alpha: M\to N$ such that $\alpha(S) \subseteq N^{\times}$: ` \begin{align*} \begin{center} \begin{tikzcd} & S^{-1}M \ar[d, dotted, "{\exists ! \tilde\alpha}"] \\ M\ar[ru, "S^{-1}\cdot"]\ar[r, "\alpha"] & N \end{tikzcd} \end{center} \end{align*} `{=html} > Strategy: define a map $M\to S^{-1}A \otimes_A M$ such that $S$ is invertible in the image to obtain a map? Show they satisfy the same universal property? - Since $M \in A{\hbox{-}}$Mod, we have an action $a\cdot m$, so define ` \begin{align*}\begin{align*} \eta: (S^{-1}A)\times M &\to (S^{-1}M) \\ \qty{ {a\over s}, m } &\mapsto {a\cdot m \over s } .\end{align*}\end{align*} `{=html} - The tensor product $S^{-1}A \otimes_A M$ makes sense. - $S^{-1}A$ is a right $A{\hbox{-}}$module by $a_0 \mapsto \qty{ {a\over s} \mapsto {a_0 a \over s}}$. - $S^{-1}M$ is a left $A{\hbox{-}}$module by $a_0 \mapsto (m \mapsto a_0 \cdot m)$ where the action comes from the $A{\hbox{-}}$module structure of $M$. - The map makes sense as an $A{\hbox{-}}$module morphism - $S^{-1}A \otimes_A M$ is a left $A{\hbox{-}}$module by $a_0 \mapsto \qty{{a\over s}\otimes m \mapsto {a_0 a \over s} \otimes m}$ - $S^{-1}M$ is a left $A{\hbox{-}}$module by $a_0 \mapsto \qty{ {m\over s } \mapsto {a_0 \cdot m \over s}}$ using the $A{\hbox{-}}$module structure on $M$. - The map makes sense as an $S^{-1}A{\hbox{-}}$module morphism - $S^{-1}A \otimes_A M$ is a left $S^{-1}A{\hbox{-}}$module by ${a_0\over s_0} \mapsto \qty{ {a\over s}\otimes m \mapsto {a_0 a \over s_0 s} \otimes m }$ - $S^{-1}M$ is a left $S^{-1}A{\hbox{-}}$module by ${a_0\over s_0} \mapsto \qty{{m \over s} \mapsto {a_0 \cdot m \over s_0 s} }$ by the $A{\hbox{-}}$module structure on $M$. - Well-defined: ? - $A{\hbox{-}}$bilinear: let $r\in A$, then ` \begin{align*}\begin{align*} \eta\qty{r \cdot {a\over s}, m} &\coloneqq\eta\qty{{r\cdot a\over s}, m} \\ &\coloneqq{\psi(r\cdot a)(m) \over s} \\ &= {r\cdot \psi(a)(m) \over s} \quad\text{since $\psi$ is a ring morphism} \\ &= {\psi(a)(r\cdot m) \over s} \quad\text{since $\psi(a)$ is a ring morphism} \\ &\coloneqq\eta\qty{ {a\over s}, r\cdot m} .\end{align*}\end{align*} `{=html} So this lifts to a map out of the tensor product. - $S^{-1}A{\hbox{-}}$bilinear? ## 1.3.P Show that the fiber product over the terminal object is the cartesian product. Solution: - Recall definition: $T$ is terminal iff every object $X$ admits a morphism $X\to T$. - Strategy: use both universal products to produce an isomorphism - Let ${\operatorname{pr}}_X, {\operatorname{pr}}_Y$ by the cartesian product projections, and ${\operatorname{pr}}_X^T, {\operatorname{pr}}_Y^T$ be the fiber product projections - Let $T_X, T_Y$ be the maps $X\to T, Y\to T$. - Since $X\times Y$ is an object in this category, it admits one unique map to $T$ ```{=tex} \begin{center} \begin{tikzcd} X\times Y\ar[r, "{\operatorname{pr}}_Y"]\ar[d, "{\operatorname{pr}}_X"']\ar[dr, "T_{X\times Y}"] & Y\ar[d, "T_Y"] \\ X\ar[r, "T_X"'] & T \end{tikzcd} \end{center} ``` - But now $T_Y \circ {\operatorname{pr}}_Y: X\times Y \to T$ is another such map, so it must equal $T_{X\times Y}$. - Similarly $T_X \circ {\operatorname{pr}}_X$ is equal to $T_{X\times Y}$. - Thus $T_Y \circ {\operatorname{pr}}_Y = T_X \circ {\operatorname{pr}}_Y$, which is part of the universal property for $X\times_T Y$. - By the universal property of $X\times Y$, for every $W$ admitting maps to $X, Y$ we get the following $h_0$: `{=tex} \begin{center} \begin{tikzcd} W \ar[drr, bend left]\ar[rdd, bend right]\ar[dr, dotted, "\exists ! h_0"] & & \\ & X\times Y\ar[r, "{\operatorname{pr}}_Y"]\ar[d, "{\operatorname{pr}}_X"] & Y\ar[d, "T_Y"] \\ & X\ar[r, "T_X"] & T \end{tikzcd} \end{center}` \> Note that $T$ doesn't matter in this particular diagram. - This gives us the LHS diagram, the RHS comes from the universal property of $X\times Y$: `{=tex} \begin{center} \begin{tikzcd} X\times_T Y\ar[drr, "{\operatorname{pr}}_Y^T", bend left]\ar[rdd, "{\operatorname{pr}}_X^T", bend right]\ar[dr, dotted, "\exists ! h_0"] & & \\ & X\times Y\ar[r, "{\operatorname{pr}}_Y"]\ar[d, "{\operatorname{pr}}_X"] & Y\ar[d, "T_Y"] \\ & X\ar[r, "T_X"] & T \end{tikzcd} \begin{tikzcd} X\times Y\ar[drr, "{\operatorname{pr}}_Y", bend left]\ar[rdd, "{\operatorname{pr}}_X", bend right]\ar[dr, dotted, "\exists ! h_1"] & & \\ & X\times_T Y\ar[r, "{\operatorname{pr}}_Y^T"]\ar[d, "{\operatorname{pr}}_X^T"] & Y\ar[d, "T_Y"] \\ & X\ar[r, "T_X"] & T \end{tikzcd} \end{center}` - By commutativity, $h_0 \circ h_1 = \operatorname{id}_{X\times Y}$ and vice-versa? ## 1.3.Q Show that if the two squares in this diagram are cartesian, then then outer square is also cartesian: ```{=tex} \begin{center} \begin{tikzcd} U \ar[r]\ar[d] & V\ar[d] \\ W \ar[r]\ar[d] & X\ar[d] \\ Y \ar[r] & Z \end{tikzcd} \end{center} ``` Solution: - Need to show that given two maps $R\to V$ and $R\to Y$ such that $(V\to Z) \circ (U\to V) = (Y\to Z) \circ (R\to Y)$, then there is a unique map $R\to U$ giving a commuting diagram: `{=tex} \begin{center} \begin{tikzcd} U\ar[drr, bend left] \ar[rdd, bend right] & & \\ & R\ar[ul, dotted, "\exists !\, ?"] \ar[r]\ar[d] & V\ar[d] \\ & Y \ar[r] & Z \end{tikzcd} \end{center}` - Applying the bottom square: - Need to produce maps $R\to X$ and $R\to Y$ - We're given a map $R\to Y$ by assumption. - We can build a map $R\to X$ by taking $(V\to X) \circ (R\to V)$. - We then get a map $R\to W$: `{=tex} \begin{center} \begin{tikzcd} W\ar[drr, bend left] \ar[rdd, bend right] & & \\ & R\ar[ul, dotted, "\exists !"] \ar[r]\ar[d] & X\ar[d] \\ & Y \ar[r] & Z \end{tikzcd} \end{center}` - Applying the top square: - We have a map $R\to V$ by assumption - We have a map $R\to W$ from step 1 - We have maps $V\to X$ and $W\to X$ from the top square - We thus obtain ``` {.tikz} \usepackage{tikz-cd} \begin{document} \begin{tikzcd} U\ar[drr, bend left] \ar[rdd, bend right] & & \\ & R\ar[ul, dotted, "\exists !"] \ar[r]\ar[d] & V\ar[d] \\ & W \ar[r] & X \end{tikzcd} \end{document} ```